The students’ speaking anxiety: Psycho-social approach - Syahriana Pratiwi; Muhammad Zuhri Dj.; Hasriati Nur (Institut Agama Islam Negeri (IAIN) Bone, 2021)
This thesis presents research about “Analyzing the Students Speaking Anxiety by Using Psycho-social Approach” The sample consists of 10 students of Al-hasib class at the second grade SMA Islam Athirah Bone. The objective of this research are (1) to analyze the reduction of the students’ speaking anxiety by using psycho-social approach. (2) to know the factors that cause students of SMA Islam Athirah Bone to get anxiety in Speaking. This research uses qualitative method by analyzing data using test, observation and interview.The result of the research shows that the students of the eleventh grade of Al-hasib class of SMA Islam Athirah Bone reduces anxiety in speaking by using psycho-social approach. It supported by the existence of social interaction that are often carried out able to make students more confident and no longer anxious, Controlling the students’ emotional in studying situation, Relaxation and motivation. They get more guidance from their English teachers such as being relax, preparing the preparation before studying or perform and positive thinking. The most dominant points are relaxation and motivation.The students have some factors in anxiety, they are lack of preparation, learners’ belief about language learning, fear of making mistakes and personal and interpersonal factors. The most dominant factors are lack of preparation and fear of making mistake.